The old man - Perry, Thomas, 1947- (The Mysterious Press, 2017)
To all appearances, Dan Chase is a harmless retiree in Vermont with two big mutts and a grown daughter he keeps in touch with by phone. But most sixty-year-old widowers don't have multiple driver's licenses, savings stockpiled in banks across the country, and a bugout kit with two Beretta Nanos stashed in the spare bedroom closet. Most have not spent decades on the run. Thirty-five years ago, as a young hotshot in army intelligence, Chase was sent to Libya to covertly assist a rebel army. When the plan turned sour, Chase reacted according to his own ideas of right and wrong, triggering consequences he could never have anticipated. And someone still wants him dead because of them. Just as he had begun to think himself finally safe, Chase must reawaken his survival instincts to contend with the history he has spent his adult life trying to escape.